If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6(x-2)=1
We move all terms to the left:
-6(x-2)-(1)=0
We multiply parentheses
-6x+12-1=0
We add all the numbers together, and all the variables
-6x+11=0
We move all terms containing x to the left, all other terms to the right
-6x=-11
x=-11/-6
x=1+5/6
| -67r=2+6r | | 2=5(-7x+8)+3(x-2) | | 2x-1-3x/10+3/2=2(x-3)+1/5 | | 6(5-v8)+12=-54 | | -15=-3r-2r | | x/3+x/6+1=3x/2-1/2 | | 10800=x | | 4-(x-5)=8x-3(2x+3) | | 3x-2+1/2+x=21-2-x | | 10-x=3/2x | | 12-x/5=7 | | -15=-3n/2 | | 2+7(-2+8v)=6(8v-5)+8v | | X^2-10y+25=0 | | 4z=25*3 | | X^1-10y+25=0 | | 5⋅(x−4)=−45 | | f-6=f-8 | | 6(n+4)=-5(-8-n) | | 3/4(2/3m=24 | | 2a2-3a-27=0 | | 8(1+6x)+7(4-2x)=-3x+x | | 2⋅(x−12)=−18 | | 3(x+4)=1-8x | | 9x-15+53=12x+1 | | 2e2-3e+1=0 | | 7(6x-7)=-6x-1 | | 12x^2-168x+441=0 | | 14+6x=-2(-8x+3) | | 12x^2-168x+147=0 | | 14n+22=8(2n-10) | | 7f+18=10f-9 |